Route of administration influences the concentration of ivermectin reaching nematode parasites in the gastrointestinal tract of cattle. (December 2020) - Leathwick, D.M.; Miller, C.M.; Waghorn, T.S.; Schwendel, H.; Lifschitz, A.
Abstract: An animal trial was conducted to measure the concentrations of ivermectin occurring in abomasal and small intestinal contents and mucosa, and in the target parasites ( Ostertagia ostertagi and Cooperia oncophora ) following administration by subcutaneous, oral and pour-on routes. Twenty-five steers were infected with ivermectin-resistant isolates of O . ostertagi and C . oncophora and following patency randomly allocated to 3 treatment groups of 7 and 1 untreated control group of four. On day 0, animals in the treatment groups were administered ivermectin via the oral, injectable or pour-on routes. On days 1, 2, 3, 4, 5, 6 and 8, blood samples were collected from all live animals, one animal from each treatment group was euthanised and the abomasum and small intestine recovered. Control animals were euthanised on each of days 4, 5, 6 and 8. Samples of gastrointestinal tract organs, their contents, mucosa and parasites were collected and assayed for ivermectin concentration using HPLC. The highest plasma concentrations occurred following subcutaneous administration. In the gastrointestinal contents the highest levels occurred following oral administration, although one high value occurred following pour-on administration, which was attributed to self-licking by the treated animal. The lowest GI content levels followed subcutaneous injection. Ivermectin concentrations in the gastrointestinal mucosa were highest following subcutaneous injection. Drug levels in the abomasal parasite O . ostertagi were most closely correlated with levels in the abomasal mucosa whereas levels in the intestinal C . oncophora were most closely correlated with those in the intestinal contents. Thus, the maximun levels of drug reached C . oncophora in the small intestine following oral administration. In contrast, the highest levels of ivermectin in O . ostertagi followed subcutaneous injection. Therefore, route of administration is likely to influence the exposure to ivermectin for different parasite species. Graphical abstract: Image 1 Highlights: Ivermectin concentrations were measured in tissue and worms. Highest levels in plasma followed subcutaneous administration. Levels in tissues and worms differed between routes of administration. Exposure of Cooperia to ivermectin was maximised by oral administration. Exposure of Ostertagia to ivermectin was maximised by subcutaneous administration.